2021
DOI: 10.2147/dddt.s301417
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hepatotoxicity of Rhubarb Based on Metabolomics and Network Pharmacology

Abstract: Background Rhubarb, as a traditional Chinese medicine, is the preferred drug for the treatment of stagnation and constipation in clinical practice. It has been reported that rhubarb possesses hepatotoxicity, but its mechanism in vivo is still unclear. Methods In this study, the chemical components in rhubarb were identified based on UPLC-Q-TOF/MS combined with data postprocessing technology. The metabolic biomarkers obtained through metabolomics technology were related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…On the other hand, network pharmacology provides a new research technique for the analysis of TCM-induced toxicity. Shan Li et al (2021) identified and explored the potential targets underlying the hepatotoxicity of Rheum palmatum L. Dai et al (2020) validated the network analysis results and demonstrated that hexabromocyclododecane caused obvious hepatotoxicity via stimulating IL-6 signaling. These previous findings contribute to the possibility of predicting the underlying mechanism of bile duct injury caused by TG.…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, network pharmacology provides a new research technique for the analysis of TCM-induced toxicity. Shan Li et al (2021) identified and explored the potential targets underlying the hepatotoxicity of Rheum palmatum L. Dai et al (2020) validated the network analysis results and demonstrated that hexabromocyclododecane caused obvious hepatotoxicity via stimulating IL-6 signaling. These previous findings contribute to the possibility of predicting the underlying mechanism of bile duct injury caused by TG.…”
Section: Introductionmentioning
confidence: 82%
“…The safety AQs is another important factor to be considered in their clinical application and drug development. With the widely used as medicinal herbs and foods, the toxicity of some AQs-containing herbs, such as Rheum and Polygonum, gradually emerged due to the improper use [169,170]. The toxicity of the AQs reported in the current research mainly includes hepatotoxicity, nephrotoxicity, genotoxicity, reproductive toxicity and phototoxicity [171,172].…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, rhubarb can reduce tumor growth by inhibiting the expression of angiogenesis-related proteins, which resulting in reduction of the blood supply to tumor tissues. 16 However, the main antitumor component of rhubarb, as well as the corresponding molecular mechanism is still unclear. This study combines systemic pharmacology and multiomics bioinformatics methodology to investigate the potential chemical components, targets, target genes of rhubarb in the treatment of PTC, and discusses its mechanism to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Rhubarb might promote intracellular apoptotic signaling pathways and induce apoptosis 15 . In addition, rhubarb can reduce tumor growth by inhibiting the expression of angiogenesis‐related proteins, which resulting in reduction of the blood supply to tumor tissues 16 . However, the main antitumor component of rhubarb, as well as the corresponding molecular mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%